Improvement of beef cattle through breeding methods - Smith, W.H.; Wheat, J.D. (Kansas Agricultural Experiment Station, 2011)
The purebred Shorthorn cattle breeding project was continued during 1960 according to the breeding program adopted when the study was initiated in 1949. Two inbred lines were established and have been continued. The Wernacre Premier line in now in the fourth generation of inbreeding and the Mercury line, in the third generation. The bulls, Wernacre’s Premier and Gregg Farm’s Hoarfrost, were used as foundation sires to establish these two lives, respectively.
Keywords: Beef; Production traits; Inheritance